If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2 = 47 Reorder the terms: 2 + 5x = 47 Solving 2 + 5x = 47 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 5x = 47 + -2 Combine like terms: 2 + -2 = 0 0 + 5x = 47 + -2 5x = 47 + -2 Combine like terms: 47 + -2 = 45 5x = 45 Divide each side by '5'. x = 9 Simplifying x = 9
| x-6+2x=18 | | 2x^2+x-1=9 | | 3.6=9c | | 3*0-2(x-3)-1-11-21=4x(2-0)-7x | | 2x-4x=22 | | 5x+6y=5(x+y) | | -10+6g=110 | | 3-4x=-4-2x | | 6+3=-7 | | -3f+14=-7 | | 55+11h=240 | | 57=6M-3 | | 3a+11=8a-24 | | 2x^2+16x=20 | | 9y-y= | | x(-3)=21 | | 6h+4=24 | | -3a+5=2 | | -4r+-8=8-16r | | 5x+20=5x+20 | | 7h+15=80 | | 4.3t-4-.2c=-9 | | 6p+4=46 | | 5-6x=11+2x | | 3x-2=2x-3 | | 11=t-2.2 | | 0.666x+4-5=0.666+1 | | -3(2s-4)-12=-3(5s+3)-5 | | 8-5x=-12 | | -(h+7)=-8h | | y-4=7(x-6) | | 0.18(12)+0.03x=0.09(12+x) |